Fungsi dewan pengawas syariah dalam manajemen strategi di bank syariah - Airlangga, Fadil (Maliki Interdisciplinary Journal, 2025)
This study examines how the Shariah Supervisory Board (DPS) contributes to the strategic management of Islamic banks, particularly regarding compliance with shariah principles in their banking practices. Islamic banks face two main challenges: the risk of financial loss and the risk of Shariah non-compliance. To address these issues, DPS plays an important role in ensuring that all bank activities are aligned with the sharia guidelines set by the National Sharia Council (DSN). Using a literature study approach, this research analyzes the responsibilities and functions of DPS within the framework of Islamic bank management strategies. The analysis revealed that the DPS is crucial in supervising and assessing the bank’s products and services, advising the directors, and conducting continuous evaluation of sharia compliance. However, challenges arise from the limited legislative authority of the DPS and the lack of adequate internal audit, which may weaken the effectiveness of supervision. Therefore, this study recommends that the role of DPS be formalized and strengthened with clearer regulations, in addition to improving the competence and integrity of its members. In this way, the DPS can more effectively ensure Shariah compliance and contribute to the sustainable development of Islamic banks.